1969
DOI: 10.1103/physrevlett.22.597
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Electron Polarization in Photoemission

Abstract: 0 0 0 25-JJJ 0 a O 20-V) M LJJ K I-V) CI UJ lO-0 0 20 40 60 80 IOO TEMPERATURE, K )20 I40 FIG. 1. Temperature dependence of the yield stressin single-pass zone-refined tungsten. Specimens prepared by electrolytic dissolution, without plastic deformation. All specimens were of the same orientation.in which tests could be performed at various temperatures between 4 and 120'K. This temperature range is a relatively unexplored temperature regime for plastic deformation experiments. Some measurements of the yield s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
4

Year Published

1976
1976
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(17 citation statements)
references
References 8 publications
0
13
0
4
Order By: Relevance
“…7 Unless explicitly specified, we shall use the terms ''nonmagnetic'' and ''paramagnetic'' interchangeably, i.e., assume that they both refer to a material with no long-range ferromagnetic order and with Zeeman-split carrier spin subbands in an applied magnetic field. 8 It has been shown that electrons photoemitted from ferromagnetic gadolinium remain spin polarized (Busch et al, 1969).…”
Section: Spin-polarized Transport and Magnetoresistive Effectsmentioning
confidence: 99%
“…7 Unless explicitly specified, we shall use the terms ''nonmagnetic'' and ''paramagnetic'' interchangeably, i.e., assume that they both refer to a material with no long-range ferromagnetic order and with Zeeman-split carrier spin subbands in an applied magnetic field. 8 It has been shown that electrons photoemitted from ferromagnetic gadolinium remain spin polarized (Busch et al, 1969).…”
Section: Spin-polarized Transport and Magnetoresistive Effectsmentioning
confidence: 99%
“…More than four decades ago Siegmann et al [5] have shown that the spin-polarization of electrons photoemitted from a magnetic sample is related to its magnetization state. The 1980ies and early 90ies saw numerous studies related to the magnetism of surfaces and ultrathin films by spin-polarized photoemission by a small number of research groups.…”
mentioning
confidence: 99%
“…На рис. 4 показан фотокатод вместе с электронно-оптической систе-мой 26 . При такой геометрии из-за большого размагничивающего фактора необходимы большие поля для намагничивания образца.…”
Section: методика экспериментаunclassified
“…Моттовский детектор регистрирует лишь поперечную, т. е. перпендикулярную к направлению скорости поляризацию пуч-ка. Поэтому в случае намагничивания образца перпендикулярно к поверхности приходится преобразовывать продольную* поляризацию пучка в поперечную с помо-щью цилиндрического конденсатора 26 . Кроме того, с помощью этого конденсатора пучок электронов отклоняют от направления освещения и отсеивают фотоэлектроны с первых электродов электронно-оптической: системы.…”
Section: методика экспериментаunclassified
See 1 more Smart Citation